The limits of influence America's role in Kashmir - Schaffer, Howard B. (ADST-DACOR diplomats and diplomacy series., 2009)
"Draws on interviews, historical research, and decades of experience in South Asia to explain and evaluate three generations of U.S. activities and policies toward Kashmir. Brings the discussion up to the current day, concluding with recommendations on the role Washington might usefully play in resolving the long-simmering dispute"--Provided by publisher.